2021
DOI: 10.1002/jcsm.12876
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome‐wide association study of sarcopenia: findings from the Hertfordshire Sarcopenia Study (HSS)

Abstract: Background Sarcopenia is the age‐related loss of muscle mass, strength, and function. Epigenetic processes such as DNA methylation, which integrate both genetic and environmental exposures, have been suggested to contribute to the development of sarcopenia. This study aimed to determine whether differences in the muscle methylome are associated with sarcopenia and its component measures: grip strength, appendicular lean mass index (ALMi), and gait speed. Methods Using the Infinium Human MethylationEPIC BeadChi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Thus, variation in methylation due to HIV serostatus was selected out when using MEAT but was apparent in the genome-wide analyses (Figure 2). In line with this rationale, no study using MEAT, including the present one, has identified associations between SkM epigenetic age and sarcopenia (Antoun et al, 2022), physical function (Sillanpaa et al, 2021) or exercise training (Gorski et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, variation in methylation due to HIV serostatus was selected out when using MEAT but was apparent in the genome-wide analyses (Figure 2). In line with this rationale, no study using MEAT, including the present one, has identified associations between SkM epigenetic age and sarcopenia (Antoun et al, 2022), physical function (Sillanpaa et al, 2021) or exercise training (Gorski et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
“…As noted byLindholm et al (2014), the changes in DNA methylation in response to environmental conditions (i.e., exercise) are slight when compared to disease-related conditions (i.e., HIV infection). Nonetheless, aerobic and resistance exercise training are associated with a shift toward a "younger" methylome(Voisin et al, 2023), thus supporting that exercise training triggers some effects that oppose aging.By way of genome-wide analyses, we found that DMPs were hypermethylated in PWH compared to controls before and after exercise training Antoun et al (2022). found that in SkM of older men, 53% of DMPs distinguished by the presence of sarcopenia were hypermethylated.…”
mentioning
confidence: 82%
“…Indeed, the authors demonstrated that the differentially methylated CpGs (dmCpGs) were enriched in genes involved in oxidative phosphorylation, voltage-gated calcium channels, and myotube fusion. Finally, by examining the chromatin architecture of the sarcopenia-related dmCpGs, the authors identified that they were contained at EZH2 target genes and at regions of H3K27 trimethylation [ 218 ].…”
Section: Epigenetic Changes In Aging-related Diseasesmentioning
confidence: 99%
“…In recent years, with the deepening of the research on the pathological mechanism of osteoporosis, the research on epigenetics has made significant inroad. Studies have demonstrated that epigenetic mechanisms are closely related to osteogenesis, bone remodeling, osteogenic differentiation, and other bone metabolism-related processes [ 218 ]. Reppe et al revealed an increasing level of CpG methylation in SOST gene promoter region in 27 postmenopausal women with osteoporosis compared to 36 healthy controls [ 219 ].…”
Section: Epigenetic Changes In Aging-related Diseasesmentioning
confidence: 99%
“…Several studies have reported a hypermethylated state in skeletal muscle tissue in older subjects compared to younger subjects ( Zykovich et al, 2014 ; Turner et al, 2020 ). There are multiple epigenome-wide association studies (EWAS) of sarcopenia or muscle mass and strength among people of European ancestry ( Livshits et al, 2016 ; Voisin et al, 2021 ; Antoun et al, 2022 ). These studies have identified many CpG loci and differentially methylated regions (DMRs) that may be associated with muscle strength.…”
Section: Introductionmentioning
confidence: 99%